Customers’ Intention to Adopt Residential Solar Power Systems in Jordan: An Empirical Study Utilizing UTAUT2 - Qasem, Zainah (Jordan Journal of Business Administration, 2021)
This study intends to identify and understand the main aspects that could influence on the Jordanian customers’ intention to adopt residential solar power systems (SPSs). The current study recognizes the necessity of building a conceptual model covering the most critical aspects related to the adoption of SPSs. Based on a careful review of main models and theories addressing new systems and the adoption of innovations, the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) was selected to propose the current study model. Also, a focus group comprising of ten Jordanian customers and experts of SPSs was established and led to the identification of trust, awareness and perceived risk as external factors considered along with the factors of UTAUT2. A survey questionnaire was conducted to collect the required data from household customers within different regions of Jordan. According to the Structural Equation Modeling (SEM) analysis, Jordanian customers’ intention is largely predicted by the role of facilitating conditions, social influence, price value, trust, awareness and perceived risk. It is anticipated that the current study’s results add value to the SPS context and enrich literature in the related area.